Plasma TAFI Levels Influence the Clot Lysis Time in Healthy Individuals in the Presence of an Intact Intrinsic Pathway of Coagulation - Mosnier, Laurent O.; von dem Borne, Peter A. Kr.; Meijers, Joost C. M.; Bouma, Bonno N. (Thrombosis and Haemostasis, 1998)
Thrombin Activatable Fibrinolysis Inhibitor (TAFI) is a recently identified fibrinolysis inhibitor in plasma, that when converted to an enzyme potently attenuates fibrinolysis. It is activated by relatively high concentrations of thrombin that exceed the thrombin concentration required for fibrin formation. These high concentrations of thrombin are generated by the intrinsic pathway via activation of factor XI by thrombin. The down regulation of fibrinolysis by TAFI can be measured in a clot lysis assay. When the clot lysis times of healthy individuals were determined, large inter-individual differences were observed. To determine if differences in concentration of TAFI explain the variation in clot lysis between individuals, specific assays were developed for the measurement of TAFI antigen and activity in plasma. In normal plasma, there was a dose-dependent relationship between TAFI antigen and TAFI activity. There was also a correlation between clot lysis time and plasma TAFI antigen, indicating that the amount of TAFI that is activated during the clot lysis assay, is dependent on the concentration of TAFI. In the plasmas of 20 healthy individuals, clot lysis times, TAFI antigen and TAFI activity were determined. Both TAFI antigen and TAFI activity showed a significant correlation with the clot lysis time. No correlation between TAFI antigen and clot lysis time was found when the clot lysis time was determined in the presence of an antibody blocking the factor XI feedback loop. These results indicate that plasma TAFI levels influence the clot lysis time in healthy individuals in the presence of an intact intrinsic pathway of coagulation.Abbreviations: The abbreviations used are: TAFI, Thrombin Activatable Fibrinolysis Inhibitor; TAFIa, activated TAFI; CPI, carboxypeptidase inhibitor from potato tubers; CPN, carboxypeptidase N; tPA, tissue-type plasminogen activator.